The Integration and Protection of Refugees for a Durable Solution in Tanzania - Kanamugire, Jean Chrysostome (Acta Universitatis Danubius. Juridica, 2025)
This paper examines the laws and policies to host refugees, promote their rights and integrate them in Tanzania. Individuals flee their countries of origin due to wars, persecution, violation of human rights, environmental disasters or climate change. Refugees receive protection in their host countries, and they cannot be forcibly repatriated to their countries of origin against their will. Tanzania has enacted laws and made policies to protect refugee rights on its territory. Since its independence, Tanzania has exhibited generosity in receiving refugees from its neighbouring states and southern African countries. Refugees live in specific areas with limited freedom of movement. Tanzania has naturalised some refugees from Rwanda, Somalia and Burundi to provide durable solutions to their plights. However, Tanzania has changed its policies towards refugees and has engaged in forcibly repatriating some refugees from Rwanda and Burundi. Tanzania must re-evaluate its current laws and policies on refugees to ensure that refugees and asylum seekers are adequately protected. Furthermore, refugees need to find a durable solution to their plights.